A DFT study of O2 and Cl2 adsorption onto Al12N12 fullerene‐like nanocluster. Issue 5 (11th October 2017) - Shokuhi Rad, Ali; Bagheri Novir, Samaneh; Mohseni, Soheil; Ramezani Cherati, Nadia; Mirabi, Ali
Abstract: In this study, the adsorption and dissociation of chlorine and oxygen molecules on the surface of Al12 N12 nanocluster have been investigated by density functional theory (DFT). Traditional B3LYP and dispersion‐corrected (ωB97XD) functionals have been used to optimize the studied structures. One relaxed structure for adsorbed Cl2 and two for adsorbed O2 (denoted as P1 and P2 configurations) have been found. Both functionals showed strong chemisorption of O2 compared to Cl2 on nanocluster. The dispersion‐corrected (ωB97XD) binding energies of Cl2 and O2 (P1 and P2) on Al12 N12 are calculated to be −32.4 (−29.1 BSSE corrected), −60.6 (−47.0 BSSE corrected), and −217.8 (−191.4 BSSE corrected) kJ/mol, respectively. We can conclude that in the suitable configuration, the adsorption of O2 associates with significant charge transfer as well as dissociation. The Gibbs free energies of all adsorptions were calculated and their values confirm exothermic spontaneous adsorption of both molecules on nanocluster.